Using the Internationally Recognized Frameworks of Nursing Competences to address the challenges of nurse refugees without documentation - Maria Cassar (Universidad de Deusto, 2020)
Individuals seeking refuge in host countries is a global reality. Some of these individuals are qualified nurses. If, and when, the documents pertaining to a nurse qualification are not presented to the respective authorities of a host country, the challenges for these qualified nurses to secure registration and employment as nurses are numerous and often unsurmountable. Access to higher education opportunities is similarly compromised in the absence of relevant documents. This is happening against the backdrop of a widely reported global shortage of qualified nurses, and an extensive effort and investment to address this shortage in many countries. This paper explores the feasibility and appropriateness of applying internationally recognized frameworks of competences of nurses, to processes which seek to evaluate and verify the nurse training and qualification claimed by refugee nurses. The author seeks to determine whether such frameworks of nurse competences may effectively and efficiently contribute towards initiatives which are geared towards addressing the gap in (qualification) document availability, traceability, verification and reproduction of nurse refugees. A critical consideration of a few existent initiatives is presented in view of exploring, the identification of a tool which may enable a homogenous transnational approach which is consistent across salient parameters. Received: 16 April 2020 Accepted: 31 August 2020